Presynaptic Inhibition at Inhibitory Nerve Terminals. A New Synapse in the Crayfish Stretch Receptor - Nakajima, Yasuko (1973)
Previous physiological evidence has shown that the receptor neuron of the slowly adapting stretch receptor organ of crayfish receives synapses from three inhibitory axons, while the receptor muscle is innervated by both excitatory and inhibitory axons. Fine structural studies have indicated that after certain preparative procedures synaptic vesicles in the inhibitory terminals on dendrites of the receptor neuron appear small and elongate, while those in the excitatory terminals on the receptor muscle are round and larger. This study describes a new synapse between two inhibitory nerve endings on the receptor neuron. One axon, containing small elongate vesicles, forms a presynaptic chemical contact with another morphologically similar axon that, itself, presumably releases inhibitory transmitter onto the receptor neuron. A second type of presynaptic axo-axonic synapse, analogous to one previously described in another crustacean muscle, was also found between presumed inhibitory and excitatory nerve terminals on the receptor muscle. Thus, the stretch receptor has a relatively complex organization with a morphological basis for two types of presynaptic inhibition: one on excitatory terminals and the other on inhibitory terminals.